Application of Monte Carlo Simulation in Industrial Microbiological Exposure Assessment - Collado, Javier; Falcó, Antonio; Rodrigo, Dolores; Sampedro, Fernando; Pina, M. Consuelo; Martínez, Antonio (IntechOpen, 2011)
None